Migrations, citizenships, and the right and choice to play for a national football team with a focus on the Croatian national team - Iveta, Vladimir (Dve domovini, 2024)
Contemporary national football teams mirror numerous migration processes. The research was focused on the formation of football teams, examples of migrations of national team members, and changes in international rules (civil and sports citizenship, options of playing for the national team). The analysis of examples of footballers who have chosen to play for a country other than their country of birth shows multiple practices. However, the most prominent choice is to represent their parents’ country of origin. The research results contribute to studies on obtaining privileged citizenship and opportune citizenship, to integration theories, and to studies of elite migration.
Keywords: autofiction; državljanstvo; metanarrative overidentification; metapripovedna nadidentifikacija; migracije; narrative agency; nogometne reprezentance; postmigration aesthetics; pravica do izbire državljanstva; privilegirano državljanstvo; Slovenian women writers; športno državljanstvo; visual artists